2019
DOI: 10.1007/s10147-019-01478-y
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year outcomes of high-dose intensity-modulated radiation therapy for nonmetastatic prostate cancer with unfavorable risk: early initiation of salvage therapy may replace long-term adjuvant androgen deprivation

Abstract: BackgroundThe optimal timing of salvage androgen deprivation therapy (ADT) following definitive radiation therapy for prostate cancer (PCa) is unknown. This study evaluated the efficacy of early initiation of salvage-ADT (S-ADT) based on predetermined timing among patients with unfavorable PCa treated with high-dose intensity-modulated radiation therapy (IMRT).Materials and methodsHigh-risk (HR) and very-high-risk (VHR) PCa patients treated with IMRT at our institution between September 2000 and December 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…Only 5.7% (n = 6) of our patients developed grade 2 rectal bleeding at 10 years, and no GI toxicities higher than grade 3 were observed. Grade 2 rectal bleeding occurred within 4 years after IMRT, and no cases of bleeding occurred after 4 years, which was consistent with previous reports [1,19]. In contrast, we observed a continuous increase in GU toxicities, and the cumulative incidence rate of grade 2/3 GU toxicities was 14.7% at 10 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only 5.7% (n = 6) of our patients developed grade 2 rectal bleeding at 10 years, and no GI toxicities higher than grade 3 were observed. Grade 2 rectal bleeding occurred within 4 years after IMRT, and no cases of bleeding occurred after 4 years, which was consistent with previous reports [1,19]. In contrast, we observed a continuous increase in GU toxicities, and the cumulative incidence rate of grade 2/3 GU toxicities was 14.7% at 10 years.…”
Section: Discussionsupporting
confidence: 92%
“…However, these GU toxicities included urinary inconsistency or urgency, which may have developed due to aging. Similarly, most of the previous reports may have categorized these toxicities as late GU toxicities, rendering it difficult to truly evaluate radiation-induced GU toxicities [1,11,19]. Therefore, we also evaluated the occurrence of urinary bleeding and obstruction separately.…”
Section: Discussionmentioning
confidence: 99%
“…As for the site of recurrence, the frequency of local recurrence was significantly higher in patients who received RT than those who underwent RP. Aizawa et al reported that of 268 patients with high-risk prostate cancer treated with intensity-modulated radiation therapy (IMRT), 97 patients developed BCR, and among them, clinical failure was detected by CT or bone scintigraphy in only 45 patients [30]. Local recurrences might explain some of these cases where the site of recurrence could not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, single radiotherapy and combining ADT with radiotherapy were implemented to 94 prostate cancer patients in the two groups, respectively, and the results showed that compared with the reference group, the clinical effect and serum indicators of the combined group were better. T-PSA is a glycoprotein secreted by prostate glandular acinus and is present in the prostatic ductal system, where its blood epithelial barrier will be disrupted following carcinogenesis of the prostate ductal system, resulting in the rising serum content [ 24 ]. It was found in this study that the serum T-PSA of treated patients in the combined group was significantly lower than that of the reference group ( P < 0.001), indicating that the combined therapy could synergistically exert mutual promoting effects and further promote the apoptosis of cancer cells, thereby inhibiting the proliferation of cancer tissues and effectively reducing the content of serum markers, which have been proved in locally advanced prostate cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%